Implementing Multicultural Education to Strengthen Elementary School Students' Character Value of Tolerance - Ayu Rahmawati; Hadi Cahyono; Sutrisno Sutrisno (Jurnal Pemberdayaan Masyarakat, 2025)
The implementation of tolerance character education at SD Eka Tjipta 01 Telen faces challenges, ranging from educators' limited understanding of the multicultural approach to the suboptimal integration of diversity values in daily learning. This study aims to describe the process of implementing multicultural education to strengthen elementary school students' tolerance and to identify strategies, practices, and obstacles encountered in schools with heterogeneous socio-cultural backgrounds. The research used a descriptive qualitative case study with participatory observation, in-depth interviews, documentation, and field notes, involving teachers, students, and parents as primary informants. Data were analyzed using Miles and Huberman's interactive model through reduction, presentation, and conclusion drawing. The results show that tolerance values are instilled through thematic learning, habitual mutual respect, and open communication among teachers, students, and parents, helping to create an inclusive learning atmosphere and supporting early internalization of tolerance. However, limited multicultural resources and minimal teacher training remain challenges. This research contributes to the discourse on multicultural education by providing empirical evidence for developing value-based education models adaptive to diversity and local needs, emphasizing the critical role of teachers, schools, and families in shaping tolerant students.